IMATH Book sebagai Upaya Peningkatan Literasi Numerasi pada Penyelesaian Soal Cerita Matematika - Safitri, Deni; Amami, Chintia Shalaza; Aldianta, Linggar; Akhsani, Shofi Rizki; Jana, Padrul (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
IMATH Book is an interactive media in the form of an illustrated book with pictures and writing to improve students' numeracy literacy skills in understanding the solution to mathematics story problems. This service uses a contextual approach so that students can more easily understand questions, especially story questions. The results of the media expert and material expert's assessment of the IMATH Book design for class 4 with a percentage of 82.60 was in the very good category, class 5 with a percentage of 80 was in the good category, and class 6 with a percentage of 85.21 was in the very good category. Thus it can be concluded that the IMATH Book classes 4, 5, and 6 are suitable for use in class. The results of this service state that using the IMATH Book makes it easier for students to understand so that they can improve their numeracy literacy skills. In addition, students become more confident in facing, finding solutions, and making decisions about the problems they are facing.